A Comprehensive Comparison of Insulation Materials for Timber Building Systems - Bernardino M. Rocha; Marina Tenório; Jorge M. Branco; Sandra M. Silva (Energies)
The key objectives of both European Union and Portuguese policies are energy efficiency and carbon neutrality in the building sector. Timber construction offers unique advantages in achieving these goals, such as increased productivity through faster and more efficient building processes, using renewable resources with lower carbon emissions during production and throughout the lifecycle, and contributions to forest conservation. However, in many countries, timber construction remains underutilised due to concerns about its thermal and acoustic performance, fire safety, and limited availability of raw materials. This study addresses these challenges by evaluating the potential of various insulation materials, including polystyrenes, mineral wools, natural fibres, composites, and acoustic mats, for incorporation into prefabricated timber components. Key performance criteria included thermal insulation, sound absorption, fire reaction, environmental impact, and local availability. Among the materials analysed, glass wool, rock wool, and cork emerged as the most favourable options, offering excellent thermal and acoustic performance and presenting strong results in other key parameters. These findings underscore the potential of incorporating these materials into timber construction systems, contributing to developing sustainable and high-performance building solutions.